Modern money and unemployment and the law of barter - Ostrer, Isidore (London: W. H. Allen, 1964)
This book introduces a Law of Barter. Modern money is a natural development in a vast complex society, but there is a flaw in modern money which may break across the Law of Barter. It also examines how modern money works in capitalism and communism as well as dealing with budget deficit, unemployment and ensuring economic growth.
Includes index
usc 3/8/17
Loans
Keywords: Monetary policy; Economic policy; Money; Unemployment; Barter